Dyslipidemia impairs mitochondrial trafficking and function in sensory neurons. Issue 1 (13th September 2017) - Rumora, Amy E.; Lentz, Stephen I.; Hinder, Lucy M.; Jackson, Samuel W.; Valesano, Andrew; Levinson, Gideon E.; Feldman, Eva L.
Abstract : Mitochondrial trafficking plays a central role in dorsal root ganglion (DRG) neuronal cell survival and neurotransmission by transporting mitochondria from the neuronal cell body throughout the bundles of DRG axons. In type 2 diabetes (T2DM), dyslipidemia and hyperglycemia damage DRG neurons and induce mitochon‐drial dysfunction; however, the impact of free fatty acids and glucose on mitochondrial trafficking in DRG neurons remains unknown. To evaluate the impact of free fatty acids compared to hyperglycemia on mitochondrial transport, primary adult mouse DRG neuron cultures were treated with physiologic concentrations of palmitate and glucose and assessed for alterations in mitochondrial trafficking, mitochondrial membrane potential, and mitochondrial bioenergetics. Palmitate treatment significantly reduced the number of motile mitochondria in DRG axons, but physiologic concentrations of glucose did not impair mitochondrial trafficking dynamics. Palmitate‐treated DRG neurons also exhibited a reduction in mitochondrial velocity, and impaired mitochondrial trafficking correlated with mitochondrial depolarization in palmitate‐treated DRG neurons. Finally, we found differential bioenergetic effects of palmitate and glucose on resting and energetically challenged mitochondria in DRG neurons. Together, these results suggest that palmitate induces DRG neuron mitochondrial depolarization, inhibiting axonal mito‐chondrial trafficking and altering mitochondrial bioenergetic capacity.—Rumora, A. E., Lentz, S. I., Hinder, L. M., Jackson, S. W., Valesano, A., Levinson, G. E., Feldman, E. L. Dyslipidemia impairs mitochondrial trafficking and function in sensory neurons. FASEB J. 32, 195‐207 (2018). www.fasebj.org